Calculation of 4H-SiC Schottky Diode with Breakdown Voltage Up to 3 KV - Yu.Drakin, A.; B. Rybalka, S.; A. Demidov, A. (International Journal of Engineering and Technology, 2018)
The current-voltage characteristic of the 4H-SiC Schottky diode for forward and reverse current direction was calculated and simulated on the base of the theory of thermionic emission and a physical analytical model based on the Poisson equation, the diffusive and continuity equations. It is shown that as follows from the theoretical calculations and calculations carried out in ATLAS that breakdown voltage of Schottky diode more than 2 kV is provided at a thickness of 4H-SiC of epitaxial layer from 18 mm. It is established that thickness of epitaxial layer from 20 mm will provide breakdown voltage of Schottky diode more than 2 kV. In addition the current-vltage characteristic for perspective Schottky diode (with breakdown voltage ~3 kV) with thickness of 4H-SiC epitaxial layer of 20 mm, p+ ring of 30 microns wide and five rings of 5 mm wide with a gap width of 2.5 mm, JTE layer of 80 mm wide. It is shown that the diode with the above specified structure can stand breakdown voltage up to ~3 kVÂ